Vetiver Root Oil Therapy's Effectiveness in Reducing Pain in Elderly Patients with Rheumatoid Arthritis ? - Rudy Alfiyansah; Hasbi Taobah Ramdani; Tri Sutrisno (Jurnal Penelitian Pendidikan IPA, 2023)
Rheumatoid arthritis is an autoimmune joint inflammation. This illness mainly affects those over 55. Many studies have examined the therapeutic advantages of perfume root oil, a processed product, for pain relief. Ginger compresses and warm water have been studied as treatments. This study evaluated the pain reported by Lansia Garut Griya Service Unit residents before and after scented root oil therapy and its effectiveness in treating pain. The study included 13 RA patients, 10 of whom met the inclusion criteria. The study found that 60% (n=6) of men and 40% (n=4) of women had rheumatoid arthritis. (RA). Before the intervention, 70% (n=7) had moderate pain and 30% (n=3) had severe pain. H0's Wilcoxon test result can be rejected because the p-value is 0.005, below the 0.05 standard of significance. It can be concluded that pre- and post-test pain scale measurements differ. These data imply that aromatic root oil therapy reduces pain in elderly rheumatoid arthritis patients.